EP561 The effect of combined progesterone and GnRH agonist on the growth of endometrial cancer cells. (1st November 2019) - Lim, S; Lee, K.B; Hong, I-S; Lee, S-H
Abstract : Introduction/Background: Endometrial cancer can occur in young women who need to preserve their fertility. Progestin based hormonal therapy including oral progestin or levonorgestrel-containing intrauterine system can be used in this setting. We performed the present study to evaluate the effect of combined progesterone and GnRH agonist on the growth of endometrial cancer cells. Methodology: Endometrial cancer cells were obtained from the Korean cell line bank and were cultured in DMEM supplemented with 10% fetal bovine serum (FBS), 100 U/ml penicillin and 100 U/ml streptomycin at 37°C and 5% CO2 . The MTT assay was used to determine the anti-proliferative capacity of GnRH or progesterone, according to the manufacturer's protocol. Cells (1×10 4 cells/well) were seeded in 96-well plates. After 24 h of incubation, the cells were treated with GnRH or progesterone for 72 h. The viable cells were measured at 570 nm using a VersaMax microplate reader. Results: Growth potential was not changed after treatment of progesterone alone at any concentration. GnRH agonist alone and combined progesterone and GnRH agonist showed concentration-dependent growth inhibition of endometrial cells. Growth potential showed 0.8, 0.7, and 0.6 fold change compared control at concentration of GnRH agonist 100nM, 500nM, and 1µM, respectively (p<0.05). Growth potential showed 0.8, 0.7, and 0.5 fold change compared control at concentration of combine progesterone and GnRH agonist 100 nM, 500 nM, and 1µM, respectively (p<0.05). However, there was no difference of growth potential between GnRH agonist and combined progesterone and GnRH agonist. Conclusion: GnRH agonist and combined progesterone and GnRH agonist showed a significant inhibited endometrial cancer cell growth by concentration-dependent fashion. Progesterone alone did not show cancer cell growth inhibition. Disclosure: Nothing to disclose.